Pengaruh Perceived Security terhadap Pengadopsian In-App Purchase pada Aplikasi Mobile - Yhony Agus Setya Mahendra; Wing Wahyu Winarno; P. Insap Santosa (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2017)
In-App Purchase or payment system based on application is one of promising revenue model in mobile application for application developers or marketers. However, in-app purchase is placed in the lowest rate compared to other model. This paper attempts to present the analysis of in-app purchase adoption viewed from the user behavior of mobile application as consumers. This study is conducted by combining the unified theory of acceptance and use of technology approach that was developed (UTAUT2) with involving perceived security aspect. The result shows that the habit of potential users, information security assurance, and hedonic motivations of potential users are the main supporting factors in adopting in-app purchase. Those factors can be admitted as a reference in developing mobile application, in order to make in-app purchase can be accepted and used by potential users of mobile application.